Alternative investment in China - a solution for investment at a time of the modern financial crisis - Broszkiewicz, Magdalena (Alternatywne inwestycje w Chinach jako sposób lokowania środków w czasie współczesnego kryzysu finansowego, 2012)
On the modern financial markets, in conditions of crisis and decline of economic achievements, there are new possibilities for investment needed. The lower correlation of financial instruments and other assets are the best solutions for negative trends on global stock markets. The most popular alternative investments are: immovables (property, land), structurised investment (options, swaps, contracts, umbrella funds, venture capital, hedge funds), emotional investment (jewellery, art, classic cars, wine, people, stamp or coin collecting) and raw materials (gold, silver, platinum, crude oil, gas, copper, aluminum, wheat, corn, soybean, cotton, sugar, coffee, cocoa, rice, etc.). There are several reasons to place investment in the Asia-Pacific region, because of the economic situation and forecasts of market growth (also capital markets). Especially the Chinese market is interesting because of the diversity of alternative investment: properties, wine, jewellery, agricultural raw materials and because of the high savings supplies of Chinese society. The most important alternative investment in China is gold. It is the main reason why it is a good moment to make an investment in the world's gold resources. China wants the juan to be the one of the world's reserve currencies, so they buy gold in public and private transactions. Asian society is said to be one of the wealthiest in the modern economy, so their participation in the world's capital markets will be increasing, the same as the new alternative investments. There is also a new trend - the numbers of wealthy people grow faster in newly developed countries than in the old ones. Chinese interest in gold is one of the most promising active on the investment markets, also because of the amount of the most wealthy people.
Ekonomia = Economics, 2012, Nr 3 (20), s. 71-82
Keywords: alternative investment; financial crisis; international finance; inwestycje alternatywne; kryzys finansowy; finanse międzynarodowe